Language and education in Japan : unequal access to bilingualism - Kanno, Yasuko, 1965- (Palgrave studies in minority languages and communities., 2008)
In this first critical ethnography of bilingual education in Japan, Yasuko Kanno examines the relationship between school education and inequality of access to bilingualism. She provides detailed and vivid accounts of the lived experiences of teachers, students and parents at five schools in Japan: an immersion school, a Chinese ethnic school, an international school, and two state/ 'public' schools. Drawing on the concept of imagined communities, Yasuko Kanno argues that schools provide unequal access to bilingualism by envisioning different imagined communities for students of different socioeconomic classes and socializing them into these stratified imagined communities. While additive bilingualism in two socially prestigious languages is aggressively promoted for upper-middle-class students, immigrant and refugee children are subtly coerced into replacing their first language with society's dominant language.